Pendampingan Evaluasi dan Dokumentasi Proses Bisnis Desa Wisata Nglinggo - Ilsa Haruti Suryandari; P . Rubiyatno; F.A. Joko Siswanto; Fr. Reni Retno Anggraini; Erico Dwi Setyawan (LPPM UNINUS, 2021)
The purpose of this program is to assist Nglinggo Tourism Village management in documenting its business process. Tourism services in Nglinggo are currently regarded to be operated smoothly, however, without sufficient documentation, it is difficult to conduct evaluation activities. Considering the importance of evaluation in the continuous development of the tourism village, business process documentation and evaluation is conducted. This community service was conducted mostly by training and advisory activities. In the advisory activities, program team assisted the management in business process identification, analysis and evaluation, as well as documentation. This documentation phase used Business Process Modeling Notation (BPMN) while evaluation utilized Quality Evaluation Framework (QEF). The results of this activity consist of documentation of business processes which include tourist services, recap of village tourism receipts and other related services. This service is expected to help Nglinggo Tourism Village to have business process documentation as a guide in order to achieve standards in tourism services.